A high-performance environmentally friendly catalyst carrier and preparation method thereof

Hydroxypropyl-β-cyclodextrin is used to create a mesoporous alumina carrier with improved structure and porosity, addressing the limitations of traditional templates and enhancing catalytic performance in hydrodesulfurization processes.

CN118788318BActive Publication Date: 2024-12-27SHANDONG GONGQUAN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411262058.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Existing alumina carriers used in hydrodesulfurization processes have disordered pore structures and poor thermal stability, limiting their catalytic performance due to the use of traditional soft templates like polyethylene glycol and glucose, which lead to pore collapse during roasting.

Method used

The use of hydroxypropyl-β-cyclodextrin as a template and surfactant for aluminum salt and metaaluminate solutions to promote dispersion and form a mesoporous structure, enhancing the specific surface area and pore volume of the alumina carrier through a self-assembly process.

Benefits of technology

The resulting alumina carrier exhibits an ordered pore structure, high specific surface area, and improved porosity, facilitating better dispersion of active particles and enhancing the desulfurization and denitrification performance in hydroprocessing units.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure EADHE9F0KS8Z5ZNLVD3BRWPWGDXBLSDROMCQFNXB
    Figure EADHE9F0KS8Z5ZNLVD3BRWPWGDXBLSDROMCQFNXB
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalyst carrier preparation, and specifically relates to a high-performance environmentally friendly catalyst carrier and a preparation method thereof, comprising the following steps: (1) dissolving an aluminum salt and a first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; (2) dissolving aluminate and a second hydroxypropyl-β-cyclodextrin in deionized water to obtain aluminate solution; (3) heating the aluminum salt solution, and then dripping the aluminate solution to obtain a mixed solution; (4) heating to 70-90°C, standing for aging; (5) filtering, washing, drying, and calcining to obtain a high-performance environmentally friendly catalyst carrier. The present invention adds the natural organic substance hydroxypropyl-β-cyclodextrin to the solution of aluminum salt and aluminate in advance, which can promote the dispersion of the reaction product during the solution dripping process, reduce the packing density of aluminum oxide, increase the pores between particles, and then increase the specific surface area and pore size of aluminum oxide, has the characteristics of safety and environmental protection, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst carrier preparation, and specifically relates to a high-performance environmentally friendly catalyst carrier and a preparation method thereof. Background Art

[0002] The production and use of clean energy has become a common theme in the development of global energy, while the sulfur content in crude oil is getting higher and higher, so the problem of reducing sulfur content has become more difficult. The development trend of clean gasoline is low sulfur, low benzene, low aromatics and low olefins; and the main challenge of deep desulfurization of diesel is to use traditional hydrodesulfurization process to remove those sulfides that are difficult to remove. Due to the inhibitory effect of polycyclic aromatic hydrocarbons and hydrogen sulfide in diesel on deep hydrodesulfurization, deep desulfurization becomes more difficult.

[0003] The development of catalysts is mainly focused on improving the hydrogenation activity and hydrodenitrogenation activity of catalysts. The purpose is to improve the conversion rate of substances such as 4,6-dimethyldibenzothiophene and further remove nitrogen compounds. By matching catalysts with high hydrogenation activity with harsh reaction conditions, diesel with a sulfur content below 10ppm can be produced to meet the requirements of use. Low-sulfur or no-sulfur fuel oil products have become a trend worldwide, and how to adapt to this requirement has also become a test for workers. At present, workers' research on hydroprocessing catalysts has entered a new field, mainly focusing on the study of carrier properties, the preparation of new carriers, and the development of new preparation technologies.

[0004] The surface properties of alumina carriers, especially the types and quantities of surface acidity and hydroxyl groups, play a vital role in regulating the metal-carrier interaction and affecting the dispersion of the active phase. Morphology, as one of the most intuitive properties of alumina particles, can affect the chemical properties and pore structure of its surface. Therefore, it is of great value to study alumina with highly regular pore structure, large specific surface area and pore volume morphology to improve its catalytic performance in hydrodesulfurization reaction. Summary of the invention

[0005] Based on the above purpose, the present invention provides a method for preparing a high-performance environmentally friendly catalyst carrier, comprising the following steps:

[0006] (1) Under stirring conditions, dissolving aluminum salt and first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of the aluminum salt to the first hydroxypropyl-β-cyclodextrin is 1:(0.05-0.2);

[0007] (2) Under stirring conditions, dissolving aluminate and the second hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and the second hydroxypropyl-β-cyclodextrin is 1:(0.6-0.8):(0.01-0.05);

[0008] (3) heating the aluminum salt solution to 40-70°C, then adding the metaaluminate solution dropwise at a rate of 5-15 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 8-10;

[0009] (4) After the addition is complete, continue stirring for a certain period of time, then raise the temperature to 70-90°C and allow to stand for aging;

[0010] (5) The aged product is filtered, washed, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier.

[0011] Template method is a common method for preparing porous alumina carriers. Most of the existing technologies use polyethylene glycol and glucose as soft templates. CN1762579A discloses the technical content of using α, β, γ and other cyclodextrins as templates. However, the above template cannot play a dispersing role, and the pore size of the prepared product is small. It is only suitable for the alkali precipitation process of strong aluminum salts. When used in the precipitation process of metaaluminate, condensation and agglomeration will occur. Moreover, this method is a traditional "soft template" method. The obtained alumina material has a disordered "worm-like" pore structure and poor thermal stability. During the roasting process to remove the template, the pore wall crystal phase is easily transformed and accompanied by the collapse of the pore structure, and the performance improvement is limited.

[0012] The present invention selects hydroxypropyl-β-cyclodextrin as a template and surfactant for aluminum salt and metaaluminate. Hydroxypropyl-β-cyclodextrin is widely available, can be made by starch degradation, has low cost, and has the technical characteristics of safety and environmental protection. The number of hydroxyl groups in hydroxypropyl-β-cyclodextrin is higher than that in α-cyclodextrin, and it contains a hydroxypropyl structure, which not only gives cyclodextrin a branched structure, but also improves its solubility, so that hydroxypropyl-β-cyclodextrin has an annular structure with internal lipophilicity and external hydrophilicity. Compared with the common linear PEG surfactants for preparing alumina, it is more conducive to forming a loose porous structure and improving the porosity and pore size of the alumina carrier.

[0013] The present invention adds hydroxypropyl-β-cyclodextrin to the solution of aluminum salt and aluminate in advance, which can promote the dispersion of reaction products during the solution dripping process, reduce the packing density, and increase the pores between particles. Among them, the hydroxypropyl-β-cyclodextrin in the aluminum salt plays the role of a structure directing agent, and the micelles formed in advance guide the formation of a mesoporous structure through a self-assembly process with the aluminum precursor; wherein, when the mass ratio of the aluminum salt to the first hydroxypropyl-β-cyclodextrin is 1: (0.1-0.15), the obtained alumina carrier has a large specific surface area. A small amount of hydroxypropyl-β-cyclodextrin in the aluminate can play the role of a surfactant, which can promote the dispersion of the crystal phase synthesized at the moment of dripping, and promote the growth of the crystal phase to form an alumina precursor, thereby realizing the regulation of the pore structure of the obtained alumina material. Specifically, a hydrolysis reaction will occur when the aluminum source in the aluminum salt comes into contact with hydroxypropyl-β-cyclodextrin as a template. When aluminate is added dropwise, an alumina precursor will be generated. At this time, the hydroxypropyl-β-cyclodextrin dispersed in the aluminate in advance can promote the dispersion of the alumina precursor, prevent it from forming a dense structure, and increase the porosity of the alumina carrier.

[0014] Furthermore, the aluminum salt in step (1) is one or more of aluminum nitrate, aluminum chloride, and aluminum sulfate.

[0015] Furthermore, the aluminum salt concentration in the aluminum salt solution in step (1) is 7-16 g / L.

[0016] Furthermore, in step (2), the aluminate is one or more of sodium aluminate or potassium aluminate.

[0017] Furthermore, the aluminate concentration in the aluminate solution in step (2) is 5-10 g / L.

[0018] Furthermore, in step (3), a mixed solution is obtained by dropping aluminate solution at a rate of 8-12 mL / min. By controlling the dropping rate of aluminate solution, the specific surface area and porosity of the alumina carrier can be effectively adjusted. If the dropping rate is too slow, it is not conducive to the growth of crystal nuclei; if the dropping rate is too fast, a flocculent structure is easily formed, which is not conducive to the dispersion of the crystal phase and leads to the occurrence of agglomeration.

[0019] Furthermore, the stirring time in step (4) is 0.5-1h.

[0020] Furthermore, in step (5), washing is performed by alternating washing with deionized water and ethanol.

[0021] Furthermore, the calcination temperature in step (5) is 500-600° C., and the calcination time is 4-6 hours.

[0022] On the other hand, the present invention also provides a high-performance environmentally friendly catalyst carrier, which is prepared by the above-mentioned preparation method of the high-performance environmentally friendly catalyst carrier.

[0023] Beneficial effects: The present invention adds hydroxypropyl-β-cyclodextrin to the solution of aluminum salt and aluminate in advance, which can promote the dispersion of reaction products during the solution addition process, reduce the packing density, and increase the porosity between particles. A hydrolysis reaction will occur when the aluminum source in the aluminum salt contacts hydroxypropyl-β-cyclodextrin as a template. When aluminate is added dropwise, an alumina precursor will be generated. At this time, the hydroxypropyl-β-cyclodextrin dispersed in the aluminate in advance can promote the dispersion of the alumina precursor, prevent it from forming a dense structure, and increase the porosity of the precursor. The alumina carrier prepared by the present invention is different from traditional alumina. It has an ordered pore structure, a high specific surface area and pore volume, is conducive to the dispersion of active particles, has environmental protection characteristics, and has broad application prospects. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0026] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0027] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0028] The aluminum salt used in the examples and comparative examples is aluminum nitrate, and the aluminate is sodium aluminate.

[0029] Example 1

[0030] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0031] (1) Under stirring conditions, dissolving aluminum salt and first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.1; and the aluminum salt concentration in the aluminum salt solution is 7 g / L;

[0032] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.6:0.01; the concentration of aluminate in the aluminate solution is 5 g / L;

[0033] (3) heating the aluminum salt solution to 40°C, then adding the metaaluminate solution dropwise at a rate of 12 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 8;

[0034] (4) After the addition is complete, continue stirring for 0.5 h, then raise the temperature to 70 °C and allow to stand for aging;

[0035] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 500°C and the calcination time was 6 hours.

[0036] Example 2

[0037] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0038] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.15; the aluminum salt concentration in the aluminum salt solution is 16 g / L;

[0039] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.8:0.05; the concentration of aluminate in the aluminate solution is 10 g / L;

[0040] (3) heating the aluminum salt solution to 70°C, then adding the metaaluminate solution dropwise at a rate of 8 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 10;

[0041] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 90°C and allow to stand for aging;

[0042] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 600°C and the calcination time was 4 hours.

[0043] Example 3

[0044] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0045] (1) Under stirring conditions, dissolving aluminum salt and first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.1; and the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0046] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.8:0.05; the concentration of aluminate in the aluminate solution is 8 g / L;

[0047] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 9 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 8;

[0048] (4) After the addition is complete, continue stirring for 0.6 h, then raise the temperature to 75 °C and allow to stand for aging;

[0049] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 520°C, and the calcination time was 4.8 h.

[0050] Example 4

[0051] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0052] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.15; the aluminum salt concentration in the aluminum salt solution is 13 g / L;

[0053] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.6:0.01; the concentration of aluminate in the aluminate solution is 9 g / L;

[0054] (3) heating the aluminum salt solution to 60°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0055] (4) After the addition is complete, continue stirring for 0.7 h, then raise the temperature to 85 °C and allow to stand for aging;

[0056] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 580° C., and the calcination time was 5 h.

[0057] Example 5

[0058] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0059] (1) Under stirring conditions, dissolving aluminum salt and first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.14; the aluminum salt concentration in the aluminum salt solution is 14 g / L;

[0060] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.7:0.04; the concentration of aluminate in the aluminate solution is 10 g / L;

[0061] (3) heating the aluminum salt solution to 48°C, then adding the metaaluminate solution dropwise at a rate of 9 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 10;

[0062] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 88°C and allow to stand for aging;

[0063] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 570°C and the calcination time was 5 h.

[0064] Example 6

[0065] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0066] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.05; the aluminum salt concentration in the aluminum salt solution is 7 g / L;

[0067] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.65:0.05; the concentration of aluminate in the aluminate solution is 8 g / L;

[0068] (3) heating the aluminum salt solution to 55°C, then adding the metaaluminate solution dropwise at a rate of 9 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0069] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 85°C and allow to stand for aging;

[0070] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 550°C and the calcination time was 5.2 h.

[0071] Example 7

[0072] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0073] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.13; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0074] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.7:0.03; the concentration of aluminate in the aluminate solution is 8 g / L;

[0075] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0076] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0077] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0078] Example 8

[0079] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0080] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.2; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0081] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.7:0.03; the concentration of aluminate in the aluminate solution is 8 g / L;

[0082] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0083] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0084] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0085] Example 9

[0086] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0087] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.13; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0088] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.7:0.03; the concentration of aluminate in the aluminate solution is 8 g / L;

[0089] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 5 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0090] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0091] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0092] Example 10

[0093] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0094] (1) Under stirring conditions, aluminum salt and first hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to first hydroxypropyl-β-cyclodextrin is 1:0.13; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0095] (2) Under stirring conditions, aluminate and second hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and second hydroxypropyl-β-cyclodextrin is 1:0.7:0.03; the concentration of aluminate in the aluminate solution is 8 g / L;

[0096] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 15 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0097] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0098] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0099] Comparative Example 1

[0100] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0101] (1) Under stirring conditions, aluminum salt and hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminum salt solution; the mass ratio of aluminum salt to hydroxypropyl-β-cyclodextrin is 1:0.16; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0102] (2) Under stirring conditions, aluminate is dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate is 1:0.7; the concentration of aluminate in the aluminate solution is 8 g / L;

[0103] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0104] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0105] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0106] Comparative Example 2

[0107] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0108] (1) Under stirring conditions, dissolving aluminum salt in deionized water to obtain an aluminum salt solution; the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0109] (2) Under stirring conditions, aluminate and hydroxypropyl-β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and hydroxypropyl-β-cyclodextrin is 1:0.7:0.16; the concentration of aluminate in the aluminate solution is 8 g / L;

[0110] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0111] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0112] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0113] Comparative Example 3

[0114] A method for preparing a high-performance environmentally friendly catalyst carrier comprises the following steps:

[0115] (1) Under stirring conditions, dissolving aluminum salt and the first β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of the aluminum salt to the first β-cyclodextrin is 1:0.13; and the aluminum salt concentration in the aluminum salt solution is 12 g / L;

[0116] (2) Under stirring conditions, aluminate and a second β-cyclodextrin are dissolved in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and the second β-cyclodextrin is 1:0.7:0.03; the concentration of aluminate in the aluminate solution is 8 g / L;

[0117] (3) heating the aluminum salt solution to 50°C, then adding the metaaluminate solution dropwise at a rate of 10 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 9;

[0118] (4) After the addition is complete, continue stirring for 1 hour, then raise the temperature to 82°C and allow to stand for aging;

[0119] (5) The aged product was filtered, washed alternately with deionized water and ethanol, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier; the calcination temperature was 540°C, and the calcination time was 5 h.

[0120] Performance test: The specific surface area, pore size and pore volume of the high-performance environmentally friendly catalyst carriers prepared in Examples 1-10 and Comparative Examples 1-3 were tested by the BET method. A mixed impregnation solution of ammonium molybdate and basic nickel carbonate with ammonia water was prepared, and the catalyst carriers prepared in Examples 1-10 and Comparative Examples 1-3 were impregnated with active components by an equal volume impregnation method, and the impregnated catalysts were dried and calcined to obtain catalysts. The catalysts were evaluated for desulfurization and denitrification in a residual oil hydroprocessing unit, and the specific results are shown in Table 1.

[0121]

[0122] As can be seen from Table 1, the present invention selects hydroxypropyl-β-cyclodextrin as the template and surfactant of aluminum salt and metaaluminate. Comparative Example 3 uses β-cyclodextrin as the template and dispersant, and the performance is poor, indicating that hydroxypropyl-β-cyclodextrin contains a hydroxypropyl structure, which not only gives cyclodextrin a branched structure, but also improves its solubility, so that hydroxypropyl-β-cyclodextrin has an annular structure with internal lipophilicity and external hydrophilicity, which is more conducive to forming a loose porous structure, improving the porosity and pore size of the alumina carrier, and the catalyst prepared therefrom has better performance in desulfurization and denitrification on a residual oil hydroprocessing unit. Compared with Example 7, the addition method of hydroxypropyl-β-cyclodextrin in Comparative Example 1-2 is different, indicating that the main role of hydroxypropyl-β-cyclodextrin is different in different solutions. The hydroxypropyl-β-cyclodextrin in the aluminum salt plays the role of a structure directing agent, and the pre-formed micelles guide the formation of a mesoporous structure through a self-assembly process with the aluminum precursor. The small amount of hydroxypropyl-β-cyclodextrin in the aluminate can play the role of a surfactant, which can promote the dispersion of the crystalline phase synthesized instantly by dropwise addition, promote the growth of the crystalline phase to form an alumina precursor, and promote the dispersion of the alumina precursor to prevent it from forming a dense structure, thereby increasing the porosity and pore size of the alumina carrier.

[0123] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a high-performance environmentally friendly catalyst carrier, characterized in that: The following steps are involved: (1) Under stirring conditions, dissolving aluminum salt and first hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminum salt solution; the mass ratio of the aluminum salt to the first hydroxypropyl-β-cyclodextrin is 1:(0.05-0.2); (2) Under stirring conditions, dissolving aluminate and the second hydroxypropyl-β-cyclodextrin in deionized water to obtain an aluminate solution; the mass ratio of aluminum salt to aluminate and the second hydroxypropyl-β-cyclodextrin is 1:(0.6-0.8):(0.01-0.05); (3) heating the aluminum salt solution to 40-70°C, then adding the metaaluminate solution dropwise at a rate of 8-12 mL / min to obtain a mixed solution, and adjusting the pH of the mixed solution to 8-10; (4) After the addition is complete, continue stirring for a certain period of time, then raise the temperature to 70-90°C and allow to stand for aging; (5) The aged product is filtered, washed, dried, and calcined in a muffle furnace to obtain a high-performance environmentally friendly catalyst carrier.

2. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The aluminum salt in step (1) is one or more of aluminum nitrate, aluminum chloride and aluminum sulfate.

3. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The aluminum salt concentration in the aluminum salt solution of step (1) is 7-16 g / L.

4. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: In step (2), the aluminate is one or more of sodium aluminate or potassium aluminate.

5. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The aluminate concentration in the aluminate solution in step (2) is 5-10 g / L.

6. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The stirring time in step (4) is 0.5-1h.

7. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The washing in step (5) is performed by alternating washing with deionized water and ethanol.

8. The method for preparing a high-performance environmentally friendly catalyst carrier according to claim 1, characterized in that: The calcination temperature in step (5) is 500-600°C and the calcination time is 4-6h.

9. A high-performance environmentally friendly catalyst carrier, characterized in that: It is prepared by the preparation method of a high-performance environmentally friendly catalyst carrier as described in any one of claims 1-8.